Pengaruh Penggunaan Media Crossword Puzzle (Teka Teki Silang) Terhadap Kemampuan Berpikir Kritis Siswa Pada Pembelajaran IPS Kelas VI di SDN Serang 7 - Miftah Maulina Syifa; Encep Supriatna (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2022)
This research was carried out based on the problems faced by class VI students at SDN Serang 7 in social studies learning, namely the use of non-variative learning methods, where in delivering learning materials using conventional methods such as lectures and very rarely using media so that students become bored, bored, not active in learning and hinder students in developing critical thinking skills so that an alternative is needed to overcome this problem, namely using the Crossword Puzzle media (Teka Teki Silang). Media Crossword Puzzle (Teka Teki Silang) in this study aims to determine whether the media Crossword Puzzle (Teka Teki Silang) affect the critical thinking skills of grade VI students of SDN Serang 7 in social studies learning. This research is a quantitative study using the Quasi Experiment method with the research design of Nonequivalent Control Group Design. Sampling was done by non-probability sampling technique with purposive sampling. Research location at SDN Serang 7. Formulation (1) What is the initial condition of grade VI students at SDN Serang 7 before using Crossword Puzzle media? (2) What are the obstacles experienced in the social studies learning process for grade VI students at SDN Serang 7? (3) How is the effect of using Crossword Puzzle learning media on students' critical thinking skills in social science learning class VI at SDN Serang 7? The results showed from the results of calculations between the posttest experimental class and control class obtained tcount = 4.398 with dk 70. Then obtained ttable = at a significance level of 0.05 of 1.667. that tcount > ttable is 4.398 > 1.667, and the significance value is 0.000 <0.05. This means that Ha is accepted, meaning that the Crossword Puzzle learning media has an effect on the social science critical thinking skills of sixth graders at SDN Serang 7.